PENGARUH PENCEMARAN DEBU SEMEN PADA STRUKTUR DAN FUNGSI DAUN BEBERAPA JENIS TANAMAN BERDAUN LEBAR - Ahmad Taufiq; Sasmita Yuliza; Alponsin; Zuhri Syam (Bio-Lectura : Jurnal Pendidikan Biologi, 2021)
The stomatal features of the leaves of several species of various life forms that grow around the cement factory are investigated with the aim of examining the anatomical modifications of the leaves which increase their tolerance and survival in the presence of cement dust pollution. In addition, the chlorophyll content in the leaves has also been examined. In comparison, the same study has also been carried out for the composition of the same species in unaffected locations. Three different life forms of the plant were investigated over two sites: trees, represented by Polyalthia longifolia, Acacia auriculiformis, Persea americana, and Mangifera indica; shrubs by Syzygium myrtifolium, and Ixora javanica; and herbs by Rhoe and Aglaonema. The average stomata density in the affected area was 173.16 /mm2, while it could reach 244.96 /mm2 at the control site. The same trend was also shown by the chlorophyll content. The Independent T-test revealed a significant difference (p-value = 0.037). Adaptability in terms of having chlorophyll content from all three life forms at different sites was also available in this discussion. Herbs has the greatest difference between sites (0.33 μg/mL), followed by shrubs (0.31 μg/mL) and then trees (0.2 μg/mL). The Two way ANOVA test showed that both life forms and sites significantly influenced the content of chlorophyll (p-value = 0.00). However, there was no interaction between sites and life forms in influencing chlorophyll content (p value=0.652). In conclusion, In all three life forms, either stomatal density or chlorophyll content decreases with pollution.